The impact of the stapled security structure on the quality of financial disclosure: Evidence from Australian Real Estate Investment Trusts and Listed Infrastructure Funds. Issue 2 (August 2019) - Liang, Jian; Dong, Zhi
Abstract: This paper is the first study to explore whether the stapled structure influences firms' activities in earnings management (EM). Trusts and firms under stapled securities are exposed to various managerial opportunities and activities that can provide the flexibility of using EM approaches. Therefore, the stapled structure is expected to induce increased EM behavior and signal a lower level of financial disclosure quality than the unstapled structure. This empirical research analyzes a panel dataset that contains information of Australian REITs (A-REITs) and Listed Infrastructure Funds (LIFs) from the year of 2000–2017. Evidence shows that stapled A-REITs and LIFs use a greater magnitude of EM approaches than unstapled entities. The results imply that the stapled security structure may signal lower-quality of financial disclosure for firms than the unstapled security structure. This study provides additional insight into the understanding of how the security structure may impact firms' financial disclosure behavior.